The relationship between the Bay of Bengal summer monsoon retreat and early summer rainfall in East Asia - Li, Qiuchi; Liu, Lin; Yang, Yang; Yang, Guang; Duan, Yongliang; Zeng, Ai (Frontiers in Earth Science, 2024)
As the upstream region of the Asian summer monsoon, the Bay of Bengal summer monsoon (BOBSM) system has impacts on rainfall patterns in eastern Asia. In this study, we investigate the impact of the interannual variability of the BOBSM retreat on China precipitation in early summer (June) of the following year. When the BOBSM retreat occurs earlier in the previous year, we find enhanced rainfall in both the northeastern and eastern parts of China. Conversely, when the retreat of the BOBSM withdrawal is delayed in the previous year, there is a tendency for decreased rainfall in most of northeastern and eastern China, while rainfall in the northern part of the Taiwan island region tends to increase. Statistical analysis demonstrates the co-variability between China's June precipitation anomalies and preceding wind anomalies in the eastern Bay of Bengal. The results indicate a strong relationship between the preceding BOBSM retreat and China precipitation anomalies in the following June. Furthermore, the analysis suggests that the BOBSM retreat is more of an independent signal rather than an Indian Ocean Dipole event.